Distribution and concentration levels of selected heavy metals and nutrients in Sungai Tengi due to paddy plantation activities - Mohd Badroldin, Nurul Adilah (2011)
Monitoring of river water quality is one way of assessing the quality of environment. In this study, Sungai Tengi was chosen as the sampling site to assess the input of heavy metals and nutrients due to agricultural and other activities in the vicinity area into the river system and finally to the estuary. The water from Sungai Tengi was also used to irrigate the paddy fields in the Sekinchan, Sungai Besar and Tanjung Karang areas which are known as the biggest rice production areas in Selangor district. Therefore, the objectives of this study are to investigate the concentration levels of heavy metals (Cu, Zn, Fe, Pb, Ni and Cd) and nutrients (nitrate and phosphate) in water column and sediment obtained from Sungai Tengi. Besides that, the levels of heavy metals in various tissues of black tilapia in Sungai Tengi were determined. Then, the pollution status of heavy metals in sediment along Sungai Tengi was estimated using the geochemical index. A total of 16 stations were set up along the river and 3 sample types of water, sediment and fish were taken. The samplings were carried out in four stages of paddy planting processes.The ranges of heavy metals in water were Cu (0.01-0.07 mg/l), Zn (0.02-3.57 mg/l), Fe (0.17-12.96 mg/l), Pb (0.03-0.80 mg/l), Ni (0.03-0.58 mg/l) and Cd (0.00-0.07 mg/l) respectively showed significant difference (p<0.05). The ranges of heavy metals in sediment were Cu (5.24-38.55 μg/g), Zn (23.46-81.05 μg/g), Fe (6876.50-18579.01 μg/g), Pb (9.00-50.22 μg/g), Ni (5.91-22.90 μg/g) and Cd (0.06-0.85 μg/g) respectively showed significant difference (p<0.05). The ranges of nitrate in water and sediment were 0.019-0.917 mg/l and 0.132-0.877 μg/g respectively. While, the ranges of phosphate in water and sediment were 0.0101-0.0713 mg/l and 0.0303-0.2953 μg/g respectively. The levels of heavy metals in tilapia were higher compared to previous studies. The ranges are below the permissible limit except for Pb and Ni. The ranges of heavy metals in muscle of tilapia were Cu (0.86-1.91 μg/g), Zn (0.90-2.93 μg/g), Fe (2.20-7.68 μg/g), Pb (1.54-6.62 μg/g), Ni (0.69-2.00 μg/g) and Cd (0.10-0.29 μg/g) respectively showed significant difference (p<0.05). Based on geochemical fraction, the level of heavy metals are 10% due to anthropogenic loading during ploughing stages. While 100% due to natural occurring during growing stages, 13% due to anthropogenic loading during fertilizing stages and 14% due to anthropogenic loading during harvesting stages respectively. However, present study showed low range of heavy metals in surface sediment from Sungai Tengi compared to others studies. The study showed Sungai Tengi is not really contaminated by heavy metals, nitrate and phosphate in water, sediment and tilapia since it were localize due to vicinity activities. The data obtained could serve as a reference to evaluate the heavy metals, nitrate and phosphate in agricultural area.